Synthesis and Characterization of Enantiopure Tribenzotriquinacene Dimers Bearing a Platinum-Diacetylene Unit - Xu, Wen-Rong; Wang, Xin-Rui; Chow, Hak-Fun; Kuck, Dietmar (Synthesis, 2019)
A pair of enantiomerically pure metallodimers containing two deeply concave tribenzotriquinacene (TBTQ) units linked by a platinum-diacetylene unit were synthesized. Such linear metal-centered TBTQ dimers are considered as edges of metallosquares and metallocubes that bear four or eight mutually syn-oriented TBTQ bowls at their tips, respectively. The structures of the metallodimers were characterized by 1H, 13C and 31P NMR spectroscopy, ESI mass spectrometry, and circular dichroism. The single X-ray crystal structure of (+)-enantiomer confirmed the absolute configuration of the metallodimers and revealed an edge (tip-to-tip) length of 18.456 Å and an approximated syn-orientation of the two TBTQ bowls in the solid state.
Keywords: chirality; metallodimer; platinum-diacetylene; tribenzotriquinacene; X-ray crystal structure